Do not disturb - McFadden, Freida (Poisoned Pen Press, 2025)
"Quinn Alexander has committed an unthinkable crime. To avoid spending her life in prison, Quinn makes a run for it. She leaves behind her home, her job, and her family. She grabs her passport and heads for the northern border before the police can discover what she's done. But when an unexpected snowstorm forces her off the road, Quinn must take refuge at the broken-down, isolated Baxter Motel. The handsome and kindly owner, Nick Baxter, is only too happy to offer her a cheap room for the night. Unfortunately, the Baxter Motel isn't the quiet, safe haven it seemed to be. The motel has a dark and disturbing past. And in the dilapidated house across the way, the silhouette of Nick's ailing wife is always at the window. Always watching. In the morning, Quinn must leave the motel. She'll pack up her belongings and get back on the road to freedom."--Provided by publisher.